The application of Ca5B2SiO10:Eu3+ and YAl3B4O12:Ce3+,Mn2+ in dual-layer remote phosphor to enhance lumen output and color quality of WLEDs - Phan Xuan Le; Le Hung Tien (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
This study proposes a dual-layer remote phosphor structure, comprised of a green or a red phosphor layer and a yellow YAG:Ce3+ phosphor layer, to enhance color rendering index (CRI) and color quality scale (CQS) of white light-emitting diodes (WLEDs). The phosphors used in this study are green phosphor YAl3B4O12:Ce3+,Mn2+ and red phosphor Ca5B2SiO10:Eu3+. Besides, the applied WLED structure has the color temperature of 8500 K. The study demonstrates the idea of placing a green phosphor YAl3B4O12:Ce3+,Mn2+ or a red Ca5B2SiO10:Eu3+ phosphor layer on the yellow phosphor YAG:Ce3+ one. After that, the suitable concentration of Ca5B2SiO10:Eu3+ resulting in the highest color quality is determined. The obtained results showed that Ca5B2SiO10:Eu3+ is advantageous to CRI and CQS. Particularly, the values of CRI and CQS increased following the growth of Ca5B2SiO10:Eu3+ concentration, due to the rise in red light components inside WLED’s packages. Meanwhile, the luminous flux is benefited by the added green YAl3B4O12:Ce3+,Mn2+ phosphor. However, there are decreases in lumen output and color quality when the concentrations of Ca5B2SiO10:Eu3+ and YAl3B4O12:Ce3+,Mn2+ rise over the corresponding levels. This result is proved via using Mie-scattering theory and Lambert-Beer's law. In short, the findings of the research paper are valuable references for high-light-quality WLEDs fabrication.